A Critique of the Undergraduate Nursing Preceptorship Model. (8th May 2012) - Sedgwick, Monique; Harris, Suzanne
Abstract : The preceptorship model is a cornerstone of clinical undergraduate nursing education in Canadian nursing programs. Their extensive use means that nursing programs depend heavily on the availability and willingness of Registered Nurses to take on the preceptor role. However, both the health service and education industries are faced with challenges that seem to undermine the effectiveness of the preceptorship clinical model. Indeed, the unstable nature of the clinical setting as a learning environment in conjunction with faculty shortages and inadequate preparation for preceptors and supervising faculty calls us to question if the preceptorship model is able to meet student learning needs and program outcomes. In a critical analysis of preceptorship, we offer a deconstruction of the model to advance clinical nursing education discourse.